Phytochemistry, ethnopharmacology and pharmacology of the genus Empetrum: a review; Advances in Traditional Medicine; Vol. ХХ, iss. Х - Bezverkhniaia E. A. Ekaterina Aleksandrovna; Ermilova E. V. Elena Vasiljevna; Kadyrova T. V. Tatjyana Vladimirovna; Krasnov E. A. Efim Avraamovich; Brazovsky (Brazovskii) K. S. Konstantin Stanislavovich; Ponkratova A. O. Anastasiya Olegovna; Luzhanin V. G. Vladimir Gennadjevich; Belousov M. V. Mikhail Valerievich (2021, 2021)
Title screen